Case report of retroperitoneal ectopic pancreas with adrenal adenoma - Sun, Zhaochen; Chen, Tao; Zhu, Xuefeng; Geng, Jie; Sui, Chaofan; Zhang, Nan; Guo, Lingfei (Frontiers in Surgery, 2022)
Background: Ectopic pancreas is a congenital anomaly in which pancreatic tissue is anatomically separated from the main gland and without vascular or ductal continuity. A case of retroperitoneal ectopic pancreas with adrenal adenoma has never been reported. Case Presentation: A 54-year-old man found three masses in the left retroperitoneum, and two of them were resected. The pathologic findings were retroperitoneal ectopic pancreatic and adrenal adenoma. Conclusion: We report an extremely rare case of retroperitoneal ectopic pancreas and its characterization with dynamic gadolinium-enhanced MRI (magnetic resonance imaging). Keywords: ectopic pancreas, retroperitoneum, adrenal adenoma, accessory spleen, magnetic resonance imaging, imaging features